Remote Health Monitoring System Using NodeMCU(ESP8266) and Arduino - Veerraju Gampala, Suneetha Bulla, Yadla Nithin Kumar, Bheemireddy Vamsi Krishna Reddy, Yeruva Snehith Reddy, Ankem Manoj Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
IoT, also referred to as the "Internet of Things," is a network of physically connected objects, systems, and tools that have sensors, software, and other technologies integrated into them. This permits data collection and exchange via the Internet. The integration of Internet of Things (IoT) technology with healthcare monitoring systems has significantly revolutionized patient health outcomes. The IoT-based smart healthcare system using Arduino and NodeMCU to detect pulse rates and temperature involves integrating sensors, microcontrollers, and cloud services. The system uses a pulse rate sensor connected to an Arduino board and a temperature sensor connected to a NodeMCU board. The sensors gather live data, which is subsequently processed and sent to a cloud-based platform for analysis and visualization. Data transmission is achieved through the NodeMCU, which collects sensor readings and sends HTTP requests to the cloud server. Here we have used ThingSpeak for Cloud integration which configures API endpoints to receive incoming sensor data. This paper introduces a smart healthcare monitoring system based on IoT technology, utilizing Arduino and NodeMCU platforms to gather, process, and transmit crucial health information, thus enabling more advanced remote monitoring via the cloud.